1999
DOI: 10.1002/(sici)1099-0488(19990101)37:1<71::aid-polb7>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of PC/SAN blends: effect of reactive compatibilization, SAN concentration, processing, and viscosity ratio

Abstract: This article examines the effects of dispersed phase concentration, processing apparatus, viscosity ratio, and interfacial compatibilization using an SAN–amine compatibilizer on the morphology of blends of bisphenol A–polycarbonate (PC) with styrene–acrylonitrile (SAN) copolymers. For uncompatibilized blends, the dispersed phase particle size increased significantly with SAN concentration, and was found to exhibit a minimum at a viscosity ratio of approximately 0.35 for a fixed concentration of 30% SAN in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…It has been extensively shown that presence of conveniently chosen polymeric species, normally functionalized copolymers, leads to a reduction in dispersed particle size. This reduction is mainly attributed to the efficiency of these copolymers in promoting steric stabilization of second phase, suppressing the coalescence phenomena . Furthermore, an effective compatibilizer system also improves the adhesion between phases, resulting in superior mechanical properties …”
Section: Resultsmentioning
confidence: 99%
“…It has been extensively shown that presence of conveniently chosen polymeric species, normally functionalized copolymers, leads to a reduction in dispersed particle size. This reduction is mainly attributed to the efficiency of these copolymers in promoting steric stabilization of second phase, suppressing the coalescence phenomena . Furthermore, an effective compatibilizer system also improves the adhesion between phases, resulting in superior mechanical properties …”
Section: Resultsmentioning
confidence: 99%
“…It has been extensively shown that the presence of adequate copolymers at the interface of immiscible blends promotes a decrease in the disperse particle size, mainly because of the efficiency of these copolymers in promoting a steric stabilization of the particles, leading to a suppression of the coalescence phenomena 38–43. Moreover, it has also been shown that there should be a minimum concentration of these copolymers at the particle surface for this suppression to become effective.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their economic importance, blends of S/AN and PC have recently drawn a lot of scientific attention. The multifaceted field of applications for these blends runs from the automotive and electronic industries to multilayer systems 1–13. Blends of S/AN and PC are immiscible under normal conditions 14–17.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their immiscibility, unmodified blends of S/AN and PC are among the most successful multiphase materials in the automotive and electronic industries 1–6. The main problem of S/AN–PC blends is their tendency to coalesce during processing, which can result in coarse structures and inferior material properties 8–12. Even short downtimes at a processing temperature of 270°C (e.g., in injection‐molding machines) can cause a significant deterioration of the morphology 32.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation